Antioxidant Activity of The Crude Carotenoid Pigment Extract from Yellow Ambon Banana (M. parasidiaca sapientum) Peel: Its Potency as Vitamin A Supplement - Suparmi, Suparmi; Prasetya, Harka (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2012)
Background: Carotenoid pigment is one of the promising sources of provitamin A because it has been shown to have capacity to be converted into vitamin A by the body. This present study aimed at evaluating the antioxidant activity in vitro using the DPPH and assessing the encapsulation of the crude carotenoid pigment extracted from Musa parasidiaca sapientum peel.Method: The total vitamin A carotenoid in the banana peel was assessed using the double beam Varian Cary 50 spectrophotometer at 470 nm. Then it was converted to microgram per gram of the banana peel using the NAS-NRC equation. The extraction was conducted using acetone. The antioxidant activity was assessed using DPPH (1.1-difenil-2-dipikrilhidrazil). The antioxidant activity of carotenoid crude extract was compared to that of marker â-karoten antioxidant (E-Merck, No. 1.02236). IC50 values were calculated using the regression formula. The dried carotenoid crude extract was encapsulated with dextrin filler.Result: The water content level of ambon banana was 50.68 % ± 3.35 %. The peel of the yellow ambon banana has a total carotenoid of 6.203 ± 0.004 μg/g. The converted carotenoid vitamin A was 124.06 ± 0.08 IU. The IC50 value of the yellow ambon banana crude extract was 2350.3 ppm meaning higher than the marker â-caroten (565.76 ppm). The encapsulation technique increased the pigment stabilization of the yellow ambon banana which will be used for vitamin A supplement.Conclusion: The crude extract of carotenoid pigment of the yellow ambon banana peel has an antioxidant potential although it is less efficient compared to that of â-carotene. The IC50 value of the crude extract of carotenoid pigment of the yellow banana ambon is 2350.3 ppm, higher than marker â -caroten (Sains Medika, 4(1):78-88).